Marginalization of Native Language: An Effect of English Language Globalization in Bangladesh - Rahman, Muhammad Mushfiqur; Lah, Salasiah Che (Pusat Pengajian Ilmu Kemanusiaan, 2019)
Globalization of the world economy with its increasing multinational companies mostly mouthed by English Language (EL) permeates new territories as well as Native languages and cultures across the globe, particularly in the developing countries- the focal point in this study is Bangladesh. Native Language (NL) and culture in the country remain faded and suppressed in the colourful injection of EL as the vehicle of prospective moneyed life that gestures the development of individual and social treasury. Students in the learning environments eye on the safe and solvent future and woo EL which is not their mother tongue. The endeavour of embracing EL gradually leads them far away from NL and culture in Bangladesh. This creates the feelings and figurations that affect social perceptions of grievance and group conflicts (Alexander, 2012). Thus, self-interest afflicts collective identity and social sufferings in terms of NL and culture where a symptom of marginalization of Bangla language (BL) and Bangalee culture is evident with the gradual intervention of English Language Globalization (ELG) along with much-talked economic globalization. This vacillating superdiversity in language use culminates profound effects on speaker subjectivity in Bangladesh. Sociolinguistic scholarship with the concept of superdiversity in recent years undergoes the linguistic impacts of stimulated globalization in late capitalism (Hall, 2014). This research enquires people’s perception of BL and EL during ELG in postcolonial era in Bangladesh.